2019
DOI: 10.1242/bio.036566
|View full text |Cite
|
Sign up to set email alerts
|

Chromogranin A regulates neuroblastoma proliferation and phenotype

Abstract: Neuroblastoma is a commonly encountered solid tumor in early childhood with high neuroplasticity, and differentiation therapy is hypothesized to lead to tumor mass shrinkage and/or symptom relief. CgA is a tissue specific protein restricted to the diffuse neuroendocrine system, and widely expressed in neuroblastomas. Using knockdown and knockout approaches to deplete CgA levels, we demonstrated that CgA loss inhibits SH-SY5Y cell proliferation and leads to a morphological shift with increased expression of Sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…As no neurocytoma cell lines exist, we used neuroblastoma SHSY-5Y cells as a surrogate model to examine effects of PHF14 loss on anchorage-independent cell growth, an indicator of tumor cell aggressiveness and metastatic potential. Neuroblastomas are derived from migratory neural crest and manifest morphological and biochemical features of immature sympathoblasts [ 19 , 20 ]. shRNA PHF14 SHSY-5Y cells formed larger colonies than those observed in nonsense-transfected control cells (Colony number with radius > 100 μm: shRNA PHF14, 413 ± 72 vs.…”
Section: Resultsmentioning
confidence: 99%
“…As no neurocytoma cell lines exist, we used neuroblastoma SHSY-5Y cells as a surrogate model to examine effects of PHF14 loss on anchorage-independent cell growth, an indicator of tumor cell aggressiveness and metastatic potential. Neuroblastomas are derived from migratory neural crest and manifest morphological and biochemical features of immature sympathoblasts [ 19 , 20 ]. shRNA PHF14 SHSY-5Y cells formed larger colonies than those observed in nonsense-transfected control cells (Colony number with radius > 100 μm: shRNA PHF14, 413 ± 72 vs.…”
Section: Resultsmentioning
confidence: 99%
“…This study observed systematic neuropeptide anomalies as expected for an LDCV release deficit (Sirkis et al, 2013). As one example, the deficiency of CHGA is known to suppress IGF signals (Zhang et al, 2019), and indeed deficient IGF-1 levels are a feature of A-T patient blood (Nissenkorn et al, 2016). At the same time, IGF-1 enhances the secretion of CHGA (Mergler et al, 2005; Münzberg et al, 2015; Wichert et al, 2000) and of other neuropeptides (Lee et al, 1999), so it would be difficult to determine if CHGA or IGF-1 is the upstream molecule.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, serum chromogranin A levels in patients with neuroblastoma are associated with a worse outcome [31,32] and patients with advanced disease stages have higher serum levels than those with localized disease [31]. It has been reported that the reduction of chromogranin A levels by knockout approaches in neuroblastoma cells caused a reduced cell proliferation rate by inhibiting the AKT/ERK pathway, whereas in an in vivo xenograft model of neuroblastoma chromogranin A knockdown led to a more differentiated (S-type) phenotype, which is known to be associated to a more favourable outcome [33].…”
Section: Discussionmentioning
confidence: 99%